Numerical optimization on differential adjusting measures for asymmetrical degenerated warm permafrost railway embankment - Yan-Dong Hou; Wen-Yuan Lei; Shu-Hao Liang; Ming-Li Zhang; Feng-Xi Zhou (Advances in Climate Change Research, 2023)
Affected by climate warming and shady–sunny slope effect, the permafrost foundation under the railway is undergoing a significant asymmetric degradation process; research on the corresponding regulating or strengthening measures is urgently needed. Based on a well developed of numerical model, we analyzed the ‘thermal repair’ effect of three redesigned differential thermal reinforcement on the partially degraded permafrost embankment with steps. The results show that, when used as a strengthening measure, the method of laying crushed rock revetment (CRR) with different thicknesses on the sunny and shady slopes cannot completely eliminate the residual warm permafrost regions formed in the previous thermal erosion. When the TCRR scheme is adopted for reinforcement, although horizontal region from the evaporation section of thermosyphones (TPCTs) to the right side of the embankment is remarkably cooled, permafrost under the sunny slope is still deteriorating. In the long run, both ETCRR and TCECRR reinforcement schemes can produce a large range of ‘cold core’ right below the whole embankment. However, from the perspective of the simultaneous functioning range and cold storage capacity, the TCECRR scheme is signally more efficient. The thermal insulation materials in the above composite strengthening measures can not only resist the heat input in the warm season, but also improve their working efficiency by maintaining the temperature difference between the evaporation section of the heat pipe and the external environment in cold season. The addition of crushed rock revetment in TCECRR has played its thermal semiconductor effect and further improved the comprehensive thermal repair efficiency of the composite measures.